Merajut Asa Kita (Knitting Our Hope): The Role of Rebranding in Developing Binong Jati Tourism Urban Village Brand Image - Allikanaya, Primaura Meiracaesara; Hermawan, Daniel (Jurnal Administrasi Bisnis, 2024)
Binong Jati is one of the creative tourism urban villages created by the Bandung city administration as part of a program to boost the tourism industry. After 58 years, rebranding was required to alter the image of the Binong Jati knitting industrial center into the Binong Jati creative tourism urban village. This study sought to evaluate the impact of rebranding on brand image through repositioning, renaming, redesigning, and relaunch dimensions. One hundred twenty-nine visitors to the Binong Jati creative tourism urban village were polled online using quantitative research and purposive sampling. Multiple linear regression was used to analyze the data with IBM SPSS Statistics 25. According to the findings, rebranding affected brand image by 60%. The brand image was significantly impacted by repositioning, renaming, and relaunch, with relaunch having the most effect. These results can be used by management to strengthen the rebranding effort and better how the general public perceives the community.